Survival Analysis in Male Breast Cancer With Bone Metastasis Based on the SEER Database - Zhou, Xingjuan; Zhang, Junwei; Wang, Yunqing; Cao, Zhenguo (Frontiers in Oncology, 2022)
Purpose: Breast cancer (BC) has been extensively and deeply studied as the number one malignant tumor in women, but its status in male patients especially in male metastatic patients is rarely reported. Thus, this study is aimed to explore the prognosis and risk factors of male BC with bone metastasis. Patients and Methods: We searched the Surveillance, Epidemiology and End Results (SEER) database to identify all patients diagnosed with male BC with bone metastasis from 2010 to 2016. Risk factors of overall survival (OS) and cancer-specific survival (CSS) were analyzed by univariable and multivariable Cox analysis. We also drew Kaplan–Meier plots to show the correlation between independent risk factors and survival. Results: A total of 207 male BC patients with bone metastasis were included for analysis. Approximately one-third of patients also had lung metastasis. Luminal A subtype comprised 58.5% of overall patient population. These patients had a poor prognosis, with 3-year OS and CSS rates, 36.7% and 39.5%, respectively. Further analysis revealed that age ≤ 60 years old, luminal A or B, and surgery were independent predictors of prolonged OS and CSS. On Cox multivariable analysis, brain metastasis was associated with OS bot CSS. Conclusion: We identified four independent factors associated with prognosis in male BC patients with bone metastasis, namely age, tumor subtype, surgery and brain metastasis. Knowing these risk factors will help clinicians make more appropriate treatment plans.